2003
DOI: 10.4028/www.scientific.net/ssp.93.249
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure Analysis of Spherical Silicon Using X-Ray Pole Figures

Abstract: Spherical silicon can be produced directly from melted silicon allowing them to solidify into spherical shape by surface tension; several organizations have carried out trial investigation for fabricate solar cells. Spherical silicon produced by this method are generally polycrystalline and solar cells fabricated from these product are strongly affected by the crystallinity. In this report, an X-ray pole plot analysis of crystal structure of spherical silicon is described. We use pole figure measurement in X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…On the surface of group (a) silicon, we can find the horns which are characteristic of Si(1 1 1). We confirmed that the directions of horns are Si(1 1 1) by means of X-ray pole figure analysis [1]. On the surface of group (b), we can find the eruption of silicon due to the volume increase in the transformation process from liquid to solid, which was reported by Jian et al [3].…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…On the surface of group (a) silicon, we can find the horns which are characteristic of Si(1 1 1). We confirmed that the directions of horns are Si(1 1 1) by means of X-ray pole figure analysis [1]. On the surface of group (b), we can find the eruption of silicon due to the volume increase in the transformation process from liquid to solid, which was reported by Jian et al [3].…”
Section: Resultssupporting
confidence: 86%
“…The characteristics of surface image, cross-sectional image and X-ray pole figure analysis of those three groups were listed up in Table 1. The distribution and the number of the small crystals are directly measured using X-ray pole figure analysis [1]. In the case of polycrystals, the number of poles is proportional to the number of grains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We developed a dropping method to fulfill this requirement and succeeded in the extremely high speed production of Si spheres about 1 mm in diameter. 4) Moreover, we proposed a new type of spherical Si solar cell with a semi-concentration reflector system. Therefore, our spherical Si solar cells are expected to be inexpensive, because the quantity of Si spheres decreases.…”
Section: Introductionmentioning
confidence: 99%
“…We developed a dropping method to fulfill this requirement and succeeded in the high-speed production of Si spheres of about 1 mm in diameter. 4) The Si spheres are generally multicrystalline and include dislocation and point defects possibly caused by the seedless crystal growth during dropping. Processes for improving the crystal quality are necessary for the electrically active crystal defects.…”
Section: Introductionmentioning
confidence: 99%